Religious and Spiritual Values Conflicts in Queer Partnerships: Implications for Couples and Family Counselors. (July 2019) - Killian, Thomas; Peters, Harvey C.; Brottem, Lainey J.
In providing couples and family counseling to sexual/affectional and gender variant minorities (i.e., queer persons), couples and family counselors (CFCs) need to recognize that religious and spiritual identity can be salient topics. While many queer persons embrace an irreligious identity, some queer individuals embrace varied degrees of religious/spiritual identification. In a partnership, an intrarelational conflict could result when the partners do not adhere to a similar level of religiosity or spirituality. CFCs must be prepared to accept the possibility of such conflict, allow for the embrace of religious identification, and offer counseling practices that will bridge that relational gap.